Elastic solid electrolyte with lithium ion selective transmembrane transmission characteristic and preparation method thereof

A composite electrolyte with a selective lithium ion permeable outer layer encapsulating a crystalline phase is formed through electrospinning and phase separation, addressing ion conductivity and stability issues in solid-state lithium sulfur batteries.

CN120319879APending Publication Date: 2025-07-15EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202510550942.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The existing solid electrolytes cannot meet the practical application requirements of solid lithium-sulfur batteries in terms of mechanical properties and electrochemical properties, especially in terms of ion conduction properties and battery cycle life and safety.

Method used

By combining electrospinning and phase separation processes, an elastomer layer with lithium ion selective permeability is constructed to coat the fibrous continuous plastic crystal electrolyte structure, and the phase separation and fibrosis of the emulsion are stabilized by amphiphilic copolymers to form a connected plastic crystal phase lithium ion transport channel and encapsulate it.

Benefits of technology

It significantly improves the ionic conductivity of the electrolyte, enhances the cycle stability and safety of lithium batteries, achieves high room temperature ionic conductivity and excellent rate performance, and has simple preparation process and low cost characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120319879A_ABST
    Figure CN120319879A_ABST
Patent Text Reader

Abstract

The invention relates to an elastic solid electrolyte with a lithium ion selective transmembrane transmission characteristic and a preparation method thereof. The elastic solid electrolyte is composed of a component A, a component B and a component C, wherein the component A comprises 12-35 parts by weight of an amphiphilic copolymer composed of a polar chain segment and a non-polar chain segment, and the weight ratio of the polar chain segment is 5-45%; the component B is 36-60 parts by weight of plastic crystal electrolyte and is formed by dissolving plastic crystals and lithium salt, and the weight ratio of the plastic crystals to the lithium salt is 1: (0.2-0.7); and the component C comprises 20-36 parts by weight of a reactive monomer and a lithium salt, and the weight ratio of the reactive monomer to the lithium salt is 1: (0.2-0.4). The preparation method comprises the following steps: firstly, preparing a fiber network elastic solid electrolyte by virtue of electrostatic spinning induced phase separation, and coating a fibrous continuous plastic crystal B by virtue of an elastomer layer A with lithium ion selective permeability; and performing in-situ polymerization on the component C to realize gap filling to obtain the elastic solid electrolyte. The solid electrolyte not only has very high ionic conductivity, but also has high mechanical strength, and the rate capability and the cycle life of the solid lithium battery are remarkably improved and prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and particularly to an elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics and a preparation method thereof. Background Art

[0002] Solid-state lithium-sulfur batteries have advantages such as high specific energy, high safety, and low cost, making them ideal candidates for next-generation batteries. However, current solid electrolytes still cannot meet the requirements of the actual application of solid-state lithium-sulfur batteries in terms of mechanical properties and electrochemical properties.

[0003] Rubber is a type of polymer material composed of cross-linked sites binding flexible polymer chains. It is very promising to develop an elastic solid electrolyte with both ionic conductivity and mechanical strength by introducing a lithium-ion conductive component into the rubber elastomer and forming a continuous network. In the prior art, certain progress has been made in the application of composite electrolytes obtained by blending an elastic polymer and a plastic crystal electrolyte in the field of solid-state batteries. For example, Patent CN 116247289 A discloses a composite electrolyte based on the blend of an elastomeric polymer and a plastic crystal electrolyte, which achieves a high ionic conductivity (>1.0 mS / cm) through a three-dimensional network plastic crystal phase filled in the polymer matrix. Patent CN 119324251 A proposes a composite electrolyte obtained by cross-linking a polymer network to accommodate plastic crystals. Patent CN 115799661 A obtains a composite solid electrolyte through in-situ polymerization of a flexible metal-organic framework, a plastic crystal electrolyte, and polyethylene glycol diacrylate. However, although the blend structures of these composite electrolytes exhibit excellent performance in terms of ion conduction, they still have certain limitations in practical applications. Specifically, by simply mixing, the polymer phase and the plastic crystal phase are randomly distributed, which not only makes it difficult to ensure a continuous plastic crystal-based ion transport channel, but also cannot prevent the plastic crystals from contacting and eroding the electrodes (especially metal electrodes), ultimately affecting the cycle life and safety of the battery.

[0004] Therefore, it is very necessary to design and prepare a composite electrolyte with a connected plastic crystal phase lithium-ion transport channel and capable of effectively encapsulating the plastic crystal phase. Summary of the Invention

[0005] Aiming at the problems existing in the prior art, the present application provides an elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics and a preparation method thereof. By combining the electrospinning and phase separation processes, the phase separation and fibrillation of an amphiphilic copolymer-stabilized emulsion are driven by an electrospray jet, constructing a structure in which an elastomer layer with lithium-ion selective permeability encapsulates fibrous continuous plastic crystal electrolytes, significantly improving the ionic conductivity of the electrolyte. At the same time, the encapsulation structure of the plastic crystal small molecules further improves the cycle stability and safety of the lithium battery.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides an elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport, which is composed of a fiber network-based elastic solid membrane of a plastic crystal B component coated with an elastomer layer A component having lithium ion selective permeability and then in-situ polymerized with a C component. Among them, the A component is 12 to 35 parts by weight, which is an amphiphilic copolymer composed of a polar segment and a non-polar segment, and the weight ratio of the polar segment is 5 to 45%; the B component is a plastic crystal electrolyte, which is 36 to 60 parts by weight, and is composed of a plastic crystal and a lithium salt that are mutually soluble, and the weight ratio of the plastic crystal to the lithium salt is 1:0.2 to 0.7; the C component is 20 to 36 parts by weight, and is composed of a reactive monomer and a lithium salt, and the weight ratio of the reactive monomer to the lithium salt is 1:0.2 to 0.4; The room temperature ionic conductivity of the elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport is higher than 0.5 mS / cm.

[0007] Among them, the amphiphilic copolymer is one of nitrile rubber, hydrogenated nitrile rubber, ethylene-vinyl acetate copolymer, and ethylene-acrylate copolymer.

[0008] The plastic crystal is one of succinonitrile, N-methylacetamide, adiponitrile, and sulfolane.

[0009] The lithium salt is one of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, bis(fluorosulfonyl)imide lithium, lithium hexafluorophosphate, and lithium difluorooxalate borate.

[0010] The reactive monomer is one of methoxypolyethylene glycol acrylate, poly(ethylene glycol) diacrylate, vinylene carbonate, 1,3-dioxolane, and 1,3-dioxane.

[0011] A second aspect of the present invention provides a preparation method of an elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport, including the following steps: (1) Dissolve the amphiphilic copolymer in a non-polar solvent to form a polymer solution, then add 0.1 - 1 wt% of a UV initiator and 1 - 5 wt% of a crosslinking agent and mix evenly. Then add the plastic crystal electrolyte, and use a high-speed homogenizer to mix at a speed of 2000 - 5000 revolutions per minute for 8 - 15 minutes to form a uniform emulsion. (2) Use the above emulsion as the spinning solution, use an aluminum foil as the receiver, and perform electrospinning at a voltage of 18 - 30 kV. Crosslink the amphiphilic block copolymer in the fiber membrane through synchronous UV irradiation. The amphiphilic block copolymer self-assembles into a fiber cortex under the combined action of phase separation caused by solvent evaporation and electrospraying force, while the plastic crystal electrolyte forms a fiber core layer ion transport channel under the action of electrospraying force and surface tension, obtaining a fiber network-based elastomeric solid-state membrane. (3) Mix the reactive monomer, lithium salt, and thermal initiator evenly to form a precursor solution, control the dosage of the thermal initiator to be 0.5 - 3 wt% of the reactive monomer. Then suck in a sufficient amount of the precursor solution into the above fiber network-based elastomeric solid-state membrane through vacuum, and place it at 50 - 80 °C for in-situ polymerization for 12 - 36 hours to obtain an elastic solid electrolyte with the characteristics of lithium ion selective transmembrane transport.

[0012] Among them, the non-polar solvent includes one of toluene, xylene, and mesitylene.

[0013] The UV initiator includes one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-propanone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and ethyl 2,4,6-trimethylbenzoyl phenylphosphonate.

[0014] The crosslinking agent includes one of polyethylene glycol diacrylate, triallyl isocyanurate, hexanediol diacrylate, and ethylene glycol dimethacrylate.

[0015] The thermal initiator includes one of azobisisobutyronitrile, azobisisoheptonitrile, benzoyl peroxide, boron trifluoride, and trifluoromethanesulfonic acid.

[0016] Due to the adoption of the above technical solutions, the present invention has the following advantages and beneficial effects: (1) The present invention forms a fiber network-based elastic solid electrolyte with an elastomer layer with lithium ion selective permeability wrapping a fibrous continuous plastic crystal electrolyte through electrospinning-induced phase separation. This is conducive to forming a highly interconnected plastic crystal phase lithium ion transport channel and making full use of the elasticity of the rubber matrix to obtain an elastic solid electrolyte with high room temperature ionic conductivity; (2) The present invention uses an amphiphilic copolymer as the encapsulation layer of the plastic crystal electrolyte. By means of the phase separation generated by the volatilization of the non-polar solvent during the electrospinning process, the polar chain segments are located inside the encapsulation layer to stabilize the plastic crystal electrolyte, while the non-polar chain segments are located outside the encapsulation layer to form a skin layer. The structural characteristics of this elastic electrolyte encapsulation layer not only enable the transmembrane transport of lithium ions, but also effectively prevent the diffusion of plastic crystal small molecules to the outside, reducing the side reactions between small molecules and the positive and negative electrodes of the metal lithium battery, thereby improving the cycling performance of the metal lithium battery. (3) The present invention proposes a strategy of combining the electrospinning-induced phase separation technology and the in-situ polymerization method to construct an elastic solid electrolyte, which not only endows strong adhesion to the positive electrode and the metal lithium negative electrode, can form a stable interface, and the assembled solid-state metal lithium battery has excellent rate performance; at the same time, it has the characteristics of simple preparation process, low raw material cost, and easy large-scale production.

[0017] The following will combine the drawings and embodiments to describe the present invention in more detail. Description of the Drawings

[0018] Figure 1 It is a transmission electron microscope photograph of a single fiber of the fiber network-based elastic solid film prepared in Example 1.

[0019] Figure 2 It is a scanning electron microscope photograph of the fiber network-based elastic solid film prepared in Example 1 before (a) and after (b) in-situ polymerization.

[0020] Figure 3 It is the room temperature ionic conductivity of the elastic solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0021] Figure 4 It is the rate curve of the lithium-sulfur battery assembled with the elastic solid electrolyte prepared in Example 1.

[0022] Figure 5 It is the (a) charge-discharge curve and (b) 100-cycle curve of the lithium-sulfur batteries assembled with the elastic solid electrolytes prepared in Example 1 and Comparative Example 1. Detailed Embodiments

[0023] In order to illustrate the present invention more clearly, the present invention will be further described below in conjunction with preferred embodiments. Those skilled in the art should understand that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the protection scope of the present invention.

[0024] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which this application pertains. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.

[0025] The following further illustrates this application through examples. Example 1

[0026] In this example, an elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics is provided. The elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics is prepared through the following steps: (1) First, an HNBR solution is obtained by completely dissolving 0.9 g of hydrogenated nitrile butadiene rubber (HNBR), 0.045 g of crosslinking agent triallyl isocyanurate, and 0.009 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone in 8.1 g of xylene. Then, a plastic crystal electrolyte (PCE) is obtained by adding 0.6 g of lithium bis(trifluoromethanesulfonyl)imide to 2.2 g of succinonitrile and uniformly dissolving it at 60 °C. By adding PCE to the HNBR solution and homogenizing it at 3000 rpm for 10 minutes, a uniform precursor emulsion is formed; (2) Electrospinning the above emulsion at 24 kV for 8 hours while simultaneously performing UV crosslinking. During this period, HNBR self-assembles into a fiber skin under the combined action of solvent evaporation and electrostatic spraying, while PCE is encapsulated as the fiber core. Finally, a fiber network-based elastomeric solid membrane (FESM) is obtained; (3) An in-situ polymerization precursor solution is prepared by adding 0.25 g of lithium bis(trifluoromethanesulfonyl)imide to 0.8 g of methoxypolyethylene glycol acrylate and uniformly dissolving it at 60 °C. After cooling, 0.008 g of thermal initiator azobisisobutyronitrile is dissolved therein. After vacuum suction of a sufficient amount of the in-situ polymerization precursor solution, FESM is assembled with the electrode and in-situ polymerized at 60 °C for 24 hours to obtain an elastic solid electrolyte (FESE) with lithium-ion selective transmembrane transport characteristics.

[0027] The applicant observes a single fiber of the obtained FESM using a transmission electron microscope, as Figure 1As shown, the single fiber described in this embodiment has a uniform thickness, with a diameter of approximately 164 nm. A black contour with a thickness of approximately 7 nm was observed on the outer surface of the fiber, which can be attributed to the presence of the encapsulation layer. Based on the geometric model of coaxial cylinders, it can be calculated that the encapsulation layer accounts for approximately 28% of the HNBR mass in the feed. It is inferred that the remaining part of the HNBR extends into the PCE phase and composites with it. This is crucial for the stability and mechanical properties of the fiber.

[0028] The applicant further examined FESM and FESE under a microscope and obtained Figure 2 the scanning electron microscope photos shown. In Figure 2 a, FESM shows a three-dimensional interconnected structure formed by fiber overlap and fusion. This structure is conducive to the formation of highly connected ion transport channels, thus contributing to a significant improvement in ion transport performance. In Figure 2 b, the surface of FESE is smooth after in-situ polymerization of methoxypolyethylene glycol acrylate, and the internal fiber structure remains clear, indicating that the in-situ polymerization process did not damage the fiber network inside FESE.

[0029] The applicant further assembled the elastic solid electrolyte with the characteristics of lithium-ion selective transmembrane transport in this embodiment with a stainless steel gasket (SS) into a SS / SPE / SS symmetric battery and obtained Figure 3 the room temperature ionic conductivity diagram shown. FESE obtained a room temperature (25 °C) ionic conductivity as high as 1.113 mS / cm.

[0030] The applicant further assembled the elastic solid electrolyte with the characteristics of lithium-ion selective transmembrane transport in this embodiment and a sulfur cathode into a lithium-sulfur battery. The sulfur-carbon composite was obtained by ball-milling sulfur and carbon nanotubes at a mass ratio of 7:3 for 6 hours. Then, the sulfur-carbon composite and the LA136D binder were dispersed in water at a mass ratio of 98:2 and vacuum planetary mixed for 10 minutes to obtain a homogeneous slurry, which was then coated on an aluminum foil with a thickness of 100 μm and dried in a vacuum oven at 60 °C for 24 hours to obtain the positive electrode of the lithium-sulfur battery.

[0031] The applicant further assembled the above sulfur cathode into a lithium-sulfur battery (FESE battery) to test the electrochemical performance of the lithium-sulfur battery and obtained Figure 4 the rate performance of the lithium-sulfur battery shown. The FESE battery showed excellent rate performance in the current density range of 0.1, 0.2, 0.5, 1, 2, and 4 C, providing capacities of 1188, 940, 670, 531, 454, and 356 mAh g - ¹ respectively. This indicates that even at high current densities, the Li +The transport capacity also meets the requirements of the sulfur species conversion kinetics on the positive electrode side. In addition, when the current density returns to 0.1 C, the specific capacity of the FESE battery is 1126 mAh g -1 , which is not much different from the initial 1188 mAh g -1 . At the same time, the charge-discharge curves of the lithium-sulfur battery at 25 °C and a current density of 0.1 C as shown in Figure 5 (a) and the cycle curve diagram of 100 cycles as shown in Figure 5 (b) are also obtained. As shown in Figure 5 (a), the platform of the FESE battery of Example 1 at 2.05 V–1.85 V corresponds to the conversion of S8 into short-chain Li2S2 and Li2S. The observed discharge curve shows the conversion path of a typical solid-state lithium-sulfur battery, indicating that the effective blockade of FESE on the plastic crystal leads to the solid-state reaction of the positive electrode, which proves the good structural stability of FESE. As shown in Figure 5 (b), after 200 cycles, the FESE battery maintains a high specific capacity of 923 mAh g⁻¹, and the capacity retention rate reaches 78.1%. Example 2

[0032] In this example, an elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics is provided. The elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics is prepared by the following steps: (1) First, an NBR solution is obtained by completely dissolving 1.5 g of nitrile butadiene rubber (NBR), 0.075 g of cross-linking agent polyethylene glycol diacrylate, and 0.015 g of photoinitiator 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-one in 13.5 g of xylene. Then, a plastic crystal electrolyte (PCE) is obtained by adding 0.6 g of lithium bis(fluorosulfonyl)imide to 2.7 g of N-methylacetamide and uniformly dissolving it at 60 °C. By adding PCE to the NBR solution and homogenizing it at 3000 rpm for 10 minutes, a uniform precursor emulsion is formed; (2) The above emulsion is electrospun at 24 kV for 8 hours, and UV cross-linking is carried out synchronously. During this period, NBR self-assembles into a fiber skin under the combined action of solvent evaporation and electrostatic spraying, while PCE is encapsulated as a fiber core. Finally, a fiber network-based elastomeric solid membrane (FESM) is obtained; (3) The in-situ polymerization precursor solution was prepared by adding 0.28 g of lithium bis(fluorosulfonyl)imide to 1.0 g of vinylene carbonate (VC) and uniformly dissolving it at 60 °C. After cooling, 0.01 g of thermal initiator azobisisobutyronitrile was dissolved therein. After vacuum pumping an adequate amount of the in-situ polymerization precursor solution, the FESM was assembled with the electrode and in-situ polymerized at 55 °C for 24 hours to obtain an elastic solid electrolyte (FESE) with the characteristic of lithium-ion selective transmembrane transport.

[0033] The applicant further assembled the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport of this example and the sulfur cathode into a lithium-sulfur battery, and the preparation of the cathode was the same as that in Example 1. Example 3

[0034] In this example, an elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport was provided, and the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport was prepared by the following steps: (1) First, an EVA solution was obtained by completely dissolving 1.4 g of ethylene-vinyl acetate copolymer (EVA) in 12.6 g of mesitylene. Then, a plastic crystal electrolyte (PCE) was obtained by adding 0.7 g of lithium bis(trifluoromethylsulfonyl)imide to 1.0 g of adiponitrile and uniformly dissolving it at 60 °C. By adding the PCE to the EVA solution and homogenizing it at 3000 rpm for 12 minutes, a uniform precursor emulsion was formed; (2) The above emulsion was electrospun at 24 kV for 12 hours. During this period, EVA self-assembled into a fiber cortex under the combined action of solvent evaporation and electrostatic spraying, while PCE was encapsulated as the fiber core. Finally, a fiber network-based elastomeric solid membrane (FESM) was obtained. The FESM was subjected to γ-ray high-energy radiation for 12 hours to crosslink the cortical EVA; (3) The in-situ polymerization precursor solution was prepared by adding 0.36 g of lithium bis(trifluoromethylsulfonyl)imide to 0.95 g of 1,3-dioxolane and uniformly dissolving it at 60 °C. After cooling, 0.01 g of thermal initiator trifluoromethanesulfonic acid was dissolved therein. After vacuum pumping an adequate amount of the in-situ polymerization precursor solution, the FESM was assembled with the electrode and in-situ polymerized at 60 °C for 24 hours to obtain an elastic solid electrolyte (FESE) with the characteristic of lithium-ion selective transmembrane transport. Example 4

[0035] In this example, an elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport was provided, and the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport was prepared by the following steps: (1) First, an EEA solution was obtained by completely dissolving 0.8 g of ethylene-acrylate copolymer (EEA) in 7.2 g of toluene. Then, a plastic crystal electrolyte (PCE) was obtained by adding 0.7 g of lithium trifluoromethanesulfonate to 1.6 g of sulfolane and uniformly dissolving it at 60 °C. By adding PCE to the EEA solution and homogenizing it at 3000 rpm for 12 minutes, a uniform precursor emulsion was formed; (2) The above emulsion was electrospun at 20 kV for 18 hours. During this period, EEA self-assembled into a fiber cortex under the combined action of solvent evaporation and electrostatic spraying, while PCE was encapsulated as the fiber core. Finally, a fiber network-based elastomeric solid-state membrane (FESM) was obtained. The FESM was subjected to high-energy gamma-ray radiation for 12 hours to crosslink the cortical EEA; (3) An in-situ polymerization precursor solution was prepared by adding 0.22 g of lithium trifluoromethanesulfonate to 0.65 g of poly(ethylene glycol) diacrylate and uniformly dissolving it at 60 °C. After cooling, 0.007 g of the thermal initiator benzoyl peroxide was dissolved therein. After vacuum pumping a sufficient amount of the in-situ polymerization precursor solution, the FESM was assembled with the electrode and in-situ polymerized at 80 °C for 24 hours to obtain an elastic solid-state electrolyte (FESE) with lithium-ion selective transmembrane transport characteristics. Example 5

[0036] In this example, an elastic solid-state electrolyte with lithium-ion selective transmembrane transport characteristics is provided, and the elastic solid-state electrolyte with lithium-ion selective transmembrane transport characteristics is prepared by the following steps: (1) First, an HNBR solution was obtained by completely dissolving 0.8 g of hydrogenated nitrile butadiene rubber (HNBR), 0.04 g of the crosslinking agent hexanediol diacrylate, and 0.008 g of the photoinitiator 2,4,6-trimethylbenzoyl diphenylphosphine oxide in 7.2 g of xylene. Then, a plastic crystal electrolyte (PCE) was obtained by adding 0.7 g of lithium hexafluorophosphate to 2.0 g of succinonitrile and uniformly dissolving it at 60 °C. By adding PCE to the HNBR solution and homogenizing it at 3000 rpm for 10 minutes, a uniform precursor emulsion was formed; (2) The above emulsion was electrospun at 24 kV for 8 hours with simultaneous UV crosslinking. During this period, HNBR self-assembled into a fiber skin under the combined action of solvent evaporation and electrostatic spraying, while PCE was encapsulated as the fiber core. Finally, a fiber network-based elastomeric solid-state membrane (FESM) was obtained; (3) An in-situ polymerization precursor solution was prepared by adding 0.18 g of lithium hexafluorophosphate to 0.9 g of 1,3-dioxane and uniformly dissolving it at 60 °C. After cooling, 0.009 g of the thermal initiator boron trifluoride was dissolved therein. After vacuum suction of a sufficient amount of the in-situ polymerization precursor solution, the FESM was assembled with the electrode and in-situ polymerized at 60 °C for 24 hours to obtain an elastic solid electrolyte (FESE) with the characteristic of lithium-ion selective transmembrane transport.

[0037] The applicant further assembled the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport in this example and the lithium iron phosphate (LFP) cathode into a Li-LFP battery. Preparation of the cathode material: LiFePO4, carbon nanotubes, and PVDF binder were dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, ball-milled for 3 hours and vacuum planetarily mixed for 10 minutes to obtain a uniform slurry, and then coated on an aluminum foil with a thickness of 100 μm and dried in a vacuum oven at 60 °C for 24 h, followed by pressing to obtain the lithium iron phosphate cathode. Example 6

[0038] In this example, an elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport is provided, and the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport is prepared by the following steps: (1) First, an NBR solution was obtained by completely dissolving 0.9 g of nitrile rubber (NBR), 0.045 g of the crosslinking agent ethylene glycol dimethacrylate, and 0.009 g of the photoinitiator 2,4,6-trimethylbenzoyl diphenylphosphine oxide in 8.1 g of mesitylene. Then, a plastic crystal electrolyte (PCE) was obtained by adding 0.7 g of lithium bis(oxalato)borate to 2.3 g of N-methylacetamide and uniformly dissolving it at 60 °C. By adding the PCE to the NBR solution and homogenizing it at 3000 rpm for 12 minutes, a uniform precursor emulsion was formed; (2) The above emulsion was electrospun at 24 kV for 12 hours with simultaneous UV crosslinking. During this period, the NBR self-assembled into a fiber skin under the combined action of solvent evaporation and electrospraying, while the PCE was encapsulated as the fiber core. Finally, a fiber network-based elastomeric solid membrane (FESM) was obtained; (3) An in-situ polymerization precursor solution was prepared by adding 0.24 g of lithium bis(oxalato)borate to 0.9 g of 1,1,1,3,3,3-hexafluorobutyl methacrylate and uniformly dissolving it at 60 °C. After cooling, 0.009 g of the thermal initiator 2,2'-azobis(2,4-dimethylvaleronitrile) was dissolved therein. After vacuum suction of a sufficient amount of the in-situ polymerization precursor solution, the FESM was assembled with the electrode and in-situ polymerized at 55 °C for 24 hours to obtain an elastic solid electrolyte (FESE) with the characteristic of lithium-ion selective transmembrane transport.

[0039] The applicant further assembled the elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport in this embodiment and LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) cathode to form a Li-NCM battery. Preparation of the NCM811 cathode material: NCM811, carbon nanotubes, and PVDF binder were dispersed in N-methylpyrrolidone in a mass ratio of 97:1:2, ball-milled for 3 hours and vacuum planetarily mixed for 10 minutes to obtain a homogeneous slurry, and then coated on an aluminum foil with a thickness of 100 μm and dried in a vacuum oven at 60°C for 24 h, followed by pressing to obtain the NCM811 cathode. Comparative Example 1

[0040] In this comparative example, an elastic solid electrolyte prepared by a common blending casting method was provided. The preparation method of the elastic solid electrolyte was prepared through the following steps: First, an HNBR solution was obtained by completely dissolving 0.7 g of hydrogenated nitrile butadiene rubber (HNBR) in 6.3 g of xylene. Then, a plastic crystal electrolyte (PCE) was obtained by adding 0.785 g of lithium bis(trifluoromethanesulfonyl)imide to 2.7 g of succinonitrile and uniformly dissolving it at 60°C. 0.15 g of lithium bis(trifluoromethanesulfonyl)imide was added to 0.4 g of methoxypolyethylene glycol acrylate ( m PEG), and uniformly dissolved at 60°C to prepare m PEG in-situ polymerization precursor solution. After cooling, 0.001 g of thermal initiator azobisisobutyronitrile was dissolved therein. Then, the HNBR solution, PCE, and m PEG in-situ polymerization precursor solution were homogenously blended at high speed for 10 minutes, and then the solvent was evaporated at 60°C and in-situ polymerized for 24 hours to obtain a common blended elastic solid electrolyte (BESE). Comparative Example 2

[0041] In this comparative example, an elastic solid electrolyte prepared by a common blending casting method was also provided. The preparation method of the elastic solid electrolyte was prepared through the following steps: First, 0.15 g of lithium bis(trifluoromethanesulfonyl)imide was added to 0.4 g of methoxypolyethylene glycol acrylate ( m PEG), and uniformly dissolved at 60°C to prepare m PEG in-situ polymerization precursor solution. After cooling, 0.001 g of thermal initiator azobisisobutyronitrile was dissolved therein. Then, it was in-situ polymerized at 60°C for 24 hours to obtain a common blended elastic solid electrolyte (BESE).

[0042] The applicant further assembled the ordinary blended elastic solid-state electrolyte of Comparative Example 1 and Comparative Example 2 with a stainless steel gasket (SS) to form an SS / SPE / SS symmetric battery, obtaining the room temperature ionic conductivity graphs shown in Table 1 and Figure 3 It can be seen that the room temperature (25 °C) ionic conductivities of Comparative Example 1 and Comparative Example 2 are 0.010 mS cm -1 and 0.003 mS cm -1 respectively, while the ionic conductivity of the elastic solid-state electrolyte with lithium-ion selective transmembrane transport characteristics described in Example 1 is significantly higher than the former two.

[0043] The applicant further assembled the ordinary blended elastic solid-state electrolyte described in Comparative Example 1 and a sulfur cathode to form a lithium-sulfur battery (BESE battery), and the preparation of the cathode material was the same as that in Example 1. The electrochemical performance of the assembled lithium-sulfur battery was tested, obtaining the rate performance of the lithium-sulfur battery shown in Figure 4 It can be seen that the room temperature (25 °C) ionic conductivities of Comparative Example 1 and Comparative Example 2 are 0.010 mS cm

[0044] Compared with Example 1, the BESE battery showed significantly worse rate performance in the current density range of 0.1, 0.2, 0.5, 1, 2, and 4 C, providing capacities of 291, 199, 65.2, 36.5, 19.7, and 11.2 mAh g - ⁻¹ respectively. This indicates that the ionic transport performance of BESE in Comparative Example 1 clearly fails to meet the requirements of the redox kinetics on the cathode side, so many active substances cannot undergo conversion. Compared with its randomly blended structure, the elastic solid-state electrolyte with lithium-ion selective transmembrane transport characteristics described in Example 1 with highly interconnected ion transport channels has significant advantages.

[0045] The charge-discharge curves of the lithium-sulfur battery at 25 °C and a current density of 0.1 C as shown in Figure 5 (a) and the cycle graph of the lithium-sulfur battery after 100 cycles as shown in Figure 5 (b) were also obtained. As shown in Figure 5 (a), the lithium-sulfur battery assembled with the FESE described in Example 1 has a higher discharge capacity. At the same time, the overpotential of the FESE battery (237 mV) is less than that of the BESE battery in Comparative Example 1 (493 mV), which means better reversibility. As shown in Figure 5 (b), the capacity of the BESE battery in Comparative Example 1 is significantly lower than that of the FESE battery, and after 130 cycles, only a specific capacity of 75.3 mAh g⁻¹ is maintained, and the capacity retention rate is only 24.2%. This shows that the FESE in Example 1 can not only improve the utilization rate of active materials by virtue of its superior ionic transport performance, but also prevent the leakage of small molecules through the fiber encapsulation structure inside the electrolyte to ensure good chemical stability. Verification Example

[0046] In this embodiment, first, stress-strain and room-temperature ionic conductivity tests are carried out on the elastic solid electrolytes with lithium-ion selective transmembrane transport characteristics in Examples 1 to 6 and the ordinary blended elastic solid electrolytes used in the comparative examples, and the detection results shown in Table 1 are obtained.

[0047] Table 1. Mechanical strength and room-temperature ionic conductivity Sample* Mechanical strength (MPa) Room temperature ionic conductivity (mS / cm) Example 1 5.6 1.113 Example 2 6.2 0.972 Example 3 3.1 0.616 Example 4 4.4 0.895 Example 5 4.9 0.748 Example 6 5.8 0.573 Comparative Example 1 1.3 0.010 Comparative Example 2 2.1 0.003 *Note: Example 5 is a Li-LiFePO4 battery; Example 6 is a Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 battery; the others are all Li-S batteries.

[0048] As can be seen from the data in Table 1, the elastic solid electrolytes with lithium-ion selective transmembrane transport characteristics in Examples 1 to 6 have high mechanical strength and exhibit good mechanical properties, while the mechanical strength of the ordinary blended elastic solid electrolytes in the comparative examples is lower than that of the examples. In addition, the ionic conductivity of the ordinary blended elastic solid electrolyte in Comparative Example 1 is only 0.010 mScm -1 , while the ionic conductivity of the elastic solid electrolytes with lithium-ion selective transmembrane transport characteristics in Examples 1 to 6 is above 0.573 mS cm -1 , significantly higher than that of the comparative examples. Moreover, the electrochemical windows of Examples 1 to 6 are all above 4.8 V, superior to those of Comparative Examples 1 to 2, indicating that the elastic solid electrolyte with lithium-ion selective transmembrane transport characteristics has obtained excellent structural stability due to its ingenious fiber encapsulation structure.

[0049] Furthermore, the applicant assembled the electrolytes prepared in Examples 1 to 6 with the positive electrode and lithium sheets in an argon atmosphere into coin cells. The obtained coin cells were tested using a Neware battery test system to detect their cycle stability at 25 °C and a current density of 0.1 C and the rate retention of 0.5C / 0.1C, and the detection results shown in Table 2 were obtained.

[0050] Table 2. Capacity retention rate after 200 cycles at 0.1C and rate retention of 0.5C / 0.1C Sample* Capacity retention rate after 200 cycles at 0.1C (%) Rate retention rate of 0.5C / 0.1C (%) Example 1 78.1 56.4 Example 2 77.9 55.7 Example 3 82.3 58.1 Example 4 80.1 54.9 Example 5 93.4 67.2 Example 6 90.9 64.9 Comparative Example 1 24.8 22.4 Comparative Example 2 33.9 18.8 *Note: Example 5 is a Li-LiFePO4 battery; Example 6 is a Li-LiNi 0.8 Co 0.1 Mn 0.1 O2 battery; the others are all Li-S batteries.

[0051] As can be seen from the data in Table 2, the capacity retention rates of the button-type metal lithium batteries assembled with the elastic solid electrolytes having the characteristics of lithium-ion selective transmembrane transport in Examples 1 to 6 are all above 75% after 200 cycles at 0.1C, which is significantly higher than the cycle life of the comparative examples; at the same time, the rate retention rates of the button-type metal lithium batteries assembled with the elastic solid electrolytes having the characteristics of lithium-ion selective transmembrane transport in Examples 1 to 6 are all above 54.9% at 0.5C / 0.1C, which is significantly higher than the rate performance of the comparative examples.

[0052] The present invention has been described by way of example in conjunction with the accompanying drawings. Obviously, the specific implementation of the present application is not limited by the above-mentioned manner. As long as various non-substantive improvements are made by adopting the method concept and technical solution of the present application; or without improvement, the above-mentioned concept and technical solution of the present application are directly applied to other occasions, they are all within the protection scope of the present application.

Claims

1. An elastic solid electrolyte with characteristics of lithium ion selective transmembrane transport, characterized in that, It is composed of a fiber network-based elastomeric solid-state membrane in which the plastic crystal B component is coated with the elastomeric layer A component having lithium ion selective permeability, and then the C component is in-situ polymerized. Among them, the A component is 12 to 35 parts by weight, an amphiphilic copolymer composed of a polar segment and a non-polar segment, and the weight ratio of the polar segment is 5 to 45%; the B component is a plastic crystal electrolyte, 36 to 60 parts by weight, composed of a plastic crystal and a lithium salt that are mutually soluble, and the weight ratio of the plastic crystal to the lithium salt is 1:0.2 to 0.7; the C component is 20 to 36 parts by weight, composed of a reactive monomer and a lithium salt, and the weight ratio of the reactive monomer to the lithium salt is 1:0.2 to 0.4; The room temperature ionic conductivity of the elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport is higher than 0.5 mS / cm; Among them, the elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport is prepared by the following preparation method: (1) Dissolve the amphiphilic copolymer in a non-polar solvent to form a polymer solution, then add 0.1 to 1 wt% of a UV initiator and 1 to 5 wt% of a crosslinking agent and mix evenly, and then add the plastic crystal electrolyte, and use a high-speed homogenizer to mix at a speed of 2000-5000 revolutions per minute for 8-15 minutes to form a uniform emulsion; (2) Use the above emulsion as the spinning solution, use aluminum foil as the receiver, perform electrospinning at a voltage of 18-30 kV, and crosslink the amphiphilic copolymer in the fiber membrane by synchronous UV irradiation. The amphiphilic block copolymer self-assembles into a fiber cortex under the combined action of phase separation caused by solvent evaporation and electrostatic spraying force, while the plastic crystal electrolyte forms a fiber core layer ion transport channel under the action of electrostatic spraying force and surface tension to obtain a fiber network-based elastomeric solid-state membrane; (3) Mix the reactive monomer, lithium salt and thermal initiator evenly to form a precursor solution, control the amount of the thermal initiator to be 0.5 to 3 wt% of the reactive monomer, and then suck the above fiber network-based elastomeric solid-state membrane into a sufficient amount of the precursor solution through vacuum, and place it at 50-80 °C for in-situ polymerization for 12-36 hours to obtain an elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport.

2. The elastic solid electrolyte with the characteristic of lithium ion selective transmembrane transport according to claim 1, wherein: The amphiphilic copolymer is one of nitrile rubber, hydrogenated nitrile rubber, ethylene-vinyl acetate copolymer, ethylene-acrylate copolymer.

3. The elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport according to claim 1, wherein: The plastic crystal is one of succinonitrile, N-methylacetamide, adiponitrile, sulfolane.

4. The elastic solid electrolyte having the characteristics of lithium ion selective transmembrane transport according to claim 1, wherein: The lithium salt is one of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, bis(fluorosulfonyl)imide lithium, lithium hexafluorophosphate, lithium difluoro(oxalato)borate.

5. The elastic solid electrolyte with the characteristic of lithium ion selective transmembrane transport according to claim 1, wherein: The reactive monomer is one of methoxypolyethylene glycol acrylate, poly(ethylene glycol) diacrylate, vinylene carbonate, 1,3-dioxolane, 1,3-dioxane.

6. The elastic solid electrolyte with the characteristic of lithium ion selective transmembrane transport according to claim 1, wherein: The non-polar solvent includes one of toluene, xylene, and mesitylene.

7. The elastic solid electrolyte having the characteristic of lithium ion selective transmembrane transport according to claim 1, characterized in that: The ultraviolet light initiator includes one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholin-1-propanone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and ethyl 2,4,6-trimethylbenzoyl phenylphosphinate.

8. The elastic solid electrolyte with the characteristic of lithium ion selective transmembrane transport according to claim 1, wherein: The crosslinking agent includes one of polyethylene glycol diacrylate, triallyl isocyanurate, hexanediol diacrylate, and ethylene glycol dimethacrylate.

9. The elastic solid electrolyte with the characteristic of lithium-ion selective transmembrane transport according to claim 1, wherein: The thermal initiator includes one of azobisisobutyronitrile, azobisisoheptonitrile, benzoyl peroxide, boron trifluoride, and trifluoromethanesulfonic acid.

Citation Information

Patent Citations

  • In-situ solid-state metal organic framework-based solid electrolyte as well as preparation method and application thereof

    CN115799661A

  • Polymer electrolyte as well as preparation method and application thereof

    CN119324251A

Cited By

  • Hierarchical microphase separation strain enhanced ionic conductive elastomer fiber as well as preparation method and application thereof

    CN122082246A